The high-resolution infrared spectrum of fully deuterated diacetylene below 1000 cm−1. (November 2015) - Bizzocchi, Luca; Tamassia, Filippo; Esposti, Claudio Degli; Dore, Luca; Villa, Mattia; Canè, Elisabetta
Abstract: Diacetylene (HC4 H) is the simplest polyyne and has been the subject of several studies related to technology, materials, supramolecular chemistry, non-linear optics. It has been detected in space and in the atmosphere of Titan. Moreover, it is a model species to test sophisticated ab initio calculations. In this paper we report the study of the infrared spectrum of the rare isotopologue DC4 D below 1000 cm −1 . The experiment has been performed by high resolution Fourier transform infrared spectroscopy. The ν 8 fundamental band, the ν 6 + ν 9, ν 7 + ν 8, and ν 6 + ν 8 combination bands and the ν 8 + ν 9 − ν 9 hot band have been observed and analysed, providing a set of accurate spectroscopic parameters. A global fit has also been performed in order to take into account the anharmonic resonance between the v 3 = 1 and the v 8 = v 9 = 1 states. The final results obtained from the global fit show a good improvement in the spectroscopic parameters for both the upper and lower states. Abstract : Highlights: We recorded the high-resolution infrared spectrum of di-deuterated diacetylene. The spectrum was recorded by FTIR in the 450–1100 cm −1 range. A global analysis of the measured wavenumbers was performed. An extended set of spectroscopic parameters has been derived.